Peran Pendidikan Agama Islam Dalam Menumbuhkan Karakter Siswa SMK - Inayah Nurul Fajriati; Ending Bahruddin (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2021)
Islamic religious education is one of the factors that influence students' attitudes and behaviours who can transform into characters so that it becomes a habit in people's lives. The writing of this article aims to find out the learning of Islamic religious education, obtain an overview of the character of students and, to find out the extent of the influence of Islamic religious education in shaping the character of students, the research was conducted in March - June 2019 at SMK Izzatul Islam Bogor Regency. The approach used in this study is quantitative, using correlational methods, and collecting data using questionnaires and observations. The result that can be concluded in this study is the existence of a moderate correlation between Islamic religious education in shaping students' character. The result of calculations get a calculated r-value of 0.463, r table 0.244; then it can be interpreted the result into a moderate category. Therefore, it can be said that Ha is received and Ho is rejected so that it can be concluded that there is an influence between Islamic religious education in shaping the character of students. From the data of the calculation of the price of the coefficient of determination obtained by 39.69%, meaning that Islamic religious education as a variable X turns out to contribute to the character of students by 60.31%, this data can be interpreted that the character of students is not only determined by aspects of spiritual value, but 60.31% is influenced by various other aspects such as extracurricular, family, environment and so on.AbstrakPendidikan agama Islam merupakan salah satu faktor yang mempengaruhi sikap dan perilaku siswa yang dapat menjelma menjadi karakter sehingga menjadi kebiasaan dalam kehidupan bermasyarakat. Penulisan artikel ini bertujuan untuk mengetahui pembelajaran pendidikan agama Islam, memperoleh gambaran tentang karakter siswa dan, untuk mengetahui sejauh mana pengaruh pendidikan agama Islam dalam membentuk karakter siswa, penelitian dilaksanakan pada bulan Maret – Juni 2019 di SMK Izzatul Islam Kabupaten Bogor. Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif, menggunakan metode korelasional, dan pengumpulan datanya memakai kuesioner dan observasi. Adapun hasil yang dapat disimpulkan dalam penelitian ini adalah adanya korelasi yang sedang antara pendidikan agama Islam dalam membentuk karakter siswa. Hasil perhitungan mendapatkan nilai r hitung sebesar 0,463, r tabel 0,244, maka dapat diinterpretasikan hasil tersebut masuk ke kategori sedang, oleh karena itu, dapat dikatakan bahwa Ha di terima dan Ho di tolak, sehingga dapat ditarik kesimpulan bahwa adanya pengaruh antara pendidikan agama Islam dalam membentuk karakter siswa. Dari data hasil perhitungan harga koefisien determinasi diperoleh sebesar 39,69%, artinya bahwa pendidikan agama Islam yang dijadikan variabel X ternyata berkontribusi terhadap karakter siswa sebesar 60,31%, data ini dapat ditafsirkan bahwa karakter siswa bukan hanya ditentukan oleh aspek nilai spiritual saja, tapi 60,31% dipengaruhi oleh berbagai aspek lain seperti ektrakurikuler, keluarga, lingkungan dan sebagainya.